Myelin proteolipid proteins promote the interaction of oligodendrocytes and axons - Yool, Donald A.; Klugmann, Matthias; Dimou, Leda; Nave, Klaus-Armin (Journal of neuroscience research, 2001)
Although proteolipid protein (PLP) and its DM20 isoform are the major membrane proteins of CNS myelin, their absence causes surprisingly few developmental defects. In comparison, missense mutations of the X-linked Plp gene cause severe dysmyelination. Previous studies have established roles for PLP/DM20 in the formation of the intraperiod line and in maintaining axonal integrity. We now show that a normal number of oligodendrocytes are present in mice lacking PLP/DM20. However, in heterozygous females, which are natural chimeras for X-linked genes, oligodendrocytes lacking PLP/DM20 are in direct competition with wild-type oligodendrocytes that have a distinct advantage. PLP+ oligodendrocytes and PLP+ myelin sheaths make up the greater majority, and this feature is generalised in the CNS throughout life. Moreover, in the absence of PLP/DM20, a proportion of small-diameter axons fails to myelinate, remaining ensheathed but lacking a compact sheath, or show delayed myelination. These findings suggest that PLP/DM20 is also involved in the early stages of axon-oligodendrocyte interaction and wrapping of the axon.